2013
DOI: 10.1182/blood-2012-09-459313
|View full text |Cite
|
Sign up to set email alerts
|

Genomic impact of transient low-dose decitabine treatment on primary AML cells

Abstract: Key Points• Decitabine treatment of in vitro expanded primary AML samples leads to global hypomethylation.• Highly methylated CpGs are most affected by decitabineinduced hypomethylation, with little influence on transcriptional activity.Acute myeloid leukemia (AML) is characterized by dysregulated gene expression and abnormal patterns of DNA methylation; the relationship between these events is unclear. Many AML patients are now being treated with hypomethylating agents, such as decitabine (DAC), although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
132
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 47 publications
15
132
1
Order By: Relevance
“…Developments in functional screening technology have produced several assay platforms for the evaluation of responses of tumor cells to exogenous perturbations. Functional screening efforts in hematologic malignancies have often involved the culture of patient cells in conventional 2D tissue culture platforms, sometimes with conventional culture conditions (38)(39)(40) and other times using additives or feeder cell coculture that promote certain phenotypic aspects of the cells, such as preservation of primitive cell differentiation state (41) and cell proliferation (42). A key feature of our ex vivo assay is that it provides drug sensitivity data within 4 d, a time frame that can support and influence clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Developments in functional screening technology have produced several assay platforms for the evaluation of responses of tumor cells to exogenous perturbations. Functional screening efforts in hematologic malignancies have often involved the culture of patient cells in conventional 2D tissue culture platforms, sometimes with conventional culture conditions (38)(39)(40) and other times using additives or feeder cell coculture that promote certain phenotypic aspects of the cells, such as preservation of primitive cell differentiation state (41) and cell proliferation (42). A key feature of our ex vivo assay is that it provides drug sensitivity data within 4 d, a time frame that can support and influence clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using 27K or 450K methylation arrays (Tsai et al 2012;Klco et al 2013;Pandiyan et al 2013), as well as with whole genome bisulfite sequencing (Lund et al 2014) have shown that DNA demethylating agents cause global hypomethylation throughout the entire genome. However, these studies have also shown that only a small percentage of genes that undergo promoter hypomethylation actually become reactivated (Tsai et al 2012;Klco et al 2013;Pandiyan et al 2013;Lund et al 2014).…”
Section: Experimental Studies On the Effect Of Dna Hypomethylating Drugsmentioning
confidence: 99%
“…13 For all 3 samples, treatment with iCRT3 resulted in a significant decrease in the expansion of viable cells compared to control (P<0.05) (Figure 2A Figure 2B). Interestingly, treatment of this sample with iCRT3 also increased the percentage of CD34 + , CD38…”
mentioning
confidence: 99%